Rancang Bangun E-Modul Berbasis STEM-Project Based Learning (STEM-PjBL) Pada Mata Pelajaran Sistem Kendali Industri Di SMKN 1 Bukittinggi - Fadhli Harzian Syah; Muhammad Adri; Efrizon Efrizon; Titi Sriwahyuni (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to design and develop an interactive e-module based on STEM-Project Based Learning (STEM-PjBL) for the Industrial Control Systems subject at SMKN 1 Bukittinggi. This e-module is designed to address the limitations of conventional learning resources and the dominance of less interactive lecture methods, as well as to increase student engagement in learning. Using a Research and Development (R&D) approach with the 4D model (Define, Design, and product creation in Develop), this research focuses on needs analysis, content structure design, media selection, and e-module interface design. The main innovation of this e-module lies in the comprehensive integration of STEM concepts through real-world project scenarios relevant to the industry, as well as the use of interactive features from Lectora Desktop and Canva for engaging visualisation. The e-module is packaged in an Android application format (.apk) for offline accessibility. The design results indicate that this e-module has a systematic structure, interactive features, and an attractive interface, thereby holding significant potential to facilitate contextual and applied learning in Industrial Control Systems.